Interactive computer graphics : a top-down approach with OpenGL. - Angel, Edward Stanley, 1944- (Boston : Addison-Wesley, 2003)
Interactive Computer Graphics features a top-down, programming-oriented approach to computer graphics. Capitalizing upon this top-down and hands-on approach, the text quickly gets students writing interesting 3D graphics programs. Angel uses OpenGL, a graphics library supported by most workstations, and the C++ programming language, allowing students to be aware of what is happening at the lowest levels of computer-graphics programming. Each chapter is built around an application, with key principles and techniques explained as needed and in increasing detail, teaching students by example and by practice. While emphasizing applications programming, the book covers all topics required for a fundamental course in computer graphics, such as light-material interactions, shading, modeling, curves and surfaces, antialiasing, texture mapping, and compositing, as well as hardware issues. The top-down approach taken in this book enables students of computer science and engineering to generate complex interactive applications by the end of their first course, and will give them a solid background for future work or study in computer graphics.
Keywords: Computer graphics